2003
DOI: 10.1364/oe.11.002102
|View full text |Cite
|
Sign up to set email alerts
|

Reducing complexity in computational imaging systems

Abstract: Traditional methods of optical design trade optical system complexity for image quality. High quality imagers often require high system complexity. A new imaging methodology called Wavefront Coding uses aspheric optics and signal processing in order to reduce system complexity and deliver high quality imagery. An example in terms of a conformal IR imaging system is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 1 publication
0
38
0
Order By: Relevance
“…Several PMs have recently been proposed, and analysed, to produce DOF extension [10,11,12,13,14,15]. Among them the most commonly used is the cubic PM, which has a phase function of the form…”
Section: Wavefront Coding Frameworkmentioning
confidence: 99%
“…Several PMs have recently been proposed, and analysed, to produce DOF extension [10,11,12,13,14,15]. Among them the most commonly used is the cubic PM, which has a phase function of the form…”
Section: Wavefront Coding Frameworkmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] Nevertheless, it has been shown that cubic and trefoil-shaped phases are most used to achieve high-quality images when spherical aberration, 10,11) astigmatism 14,15) and high orderaberrations 15) are also present in the system. WFC can be found in many different applications such as in ophthalmic optics, [15][16][17] iris recognition, 18,19) complexity reduction in optical systems, 20) control of thermal defocus in infrared systems, 21) barcode reading, 22) and microscopy, 23) among many others. The DOF in each application can be extended by a trefoil phase at the exit pupil of the optical system, and the trade-off between the DOF and the image resolution properties is dependent on the peak-to-valley value (strength) of the phase.…”
Section: Introductionmentioning
confidence: 99%
“…1 Especially in high-resolution microscopes with large NA, the DOF is limited. 2,3 An effective solution for the problem DOF control is, therefore, of interest for general design of imaging systems, regardless the application.…”
Section: Introductionmentioning
confidence: 99%